No Paradoxical Effect of Smoking Status on Recurrent Cardiovascular Events in Patients Following Percutaneous Coronary Intervention: Thai PCI Registry - Limpijankit, Thosaphol; Chandavimol, Mann; Srimahachota, Suphot; Siriyotha, Sukanya; Thakkinstian, Ammarin; Krittayaphong, Rungroj; Sansanayudh, Nakarin (Frontiers in Cardiovascular Medicine, 2022)
Background: ‘Smoker’s paradox’ is a controversial phenomenon describing an unexpectedly favorable short-term outcome of smokers post percutaneous coronary intervention (PCI). This study aimed to evaluate the effect of smoking status on recurrent major cardiovascular events (MACEs) in patients who recently underwent PCI and determine if it was paradoxical. Methods: This study utilized data from the nationwide Thai PCI registry, enrolling patients during 2018-19. Our study factor was smoking status, classified as current-, ex-, and never smokers. The outcome of interest was time to occurrence of a composite of MACEs (i.e., all-cause death, myocardial infarction (MI), stroke, and unplanned revascularization) evaluated at about 1-year post-PCI. A propensity score model by inverse probability weighting with regression adjustment was used to estimate smoking effect on MACE occurrence. Results: Current-, ex-, and never-smokers were found in 23%, 32% and 45%, respectively, of the 22,741 subjects. Smokers were younger, more frequently male, and had fewer traditional atherosclerotic risk factors. Current smokers presented more frequently with ST-elevation MIs and cardiogenic shock (54% and 14.6%, respectively) than did non-smokers. The MACE rates were 1.9, 1.2, and 1.6 per 100 patients per month in the current-smokers, ex-smokers, and never-smokers, respectively. After applying a propensity score, patients with current- and ex-smoking histories developed onset of recurrent MACEs significantly sooner than did never smokers with median times of 4.4 vs. 4.9 vs. 13.5 months (P<0.001), respectively. Conclusions: ‘Smoker’s paradox’ was not observed in our patient population. Current- and ex-smokers were prone to develop earlier onset of a post-PCI MACEs than non-smokers and need a smoke cessation program for further prevention.